Feeding Systems and Host Breeds Influence Ruminal Fermentation, Methane Production, Microbial Diversity and Metagenomic Gene Abundance - Bharanidharan, Rajaraman; Lee, Chang Hyun; Thirugnanasambantham, Krishnaraj; Ibidhi, Ridha; Woo, Yang Won; Lee, Hong-Gu; Kim, Jong Geun; Kim, Kyoung Hoon (Frontiers in Microbiology, 2021)
Our previous research revealed the advantages of separate feeding (SF) systems compared to total mixed ration (TMR) in terms of ruminal methane (CH4) production. The purpose of this experiment was to confirm the advantage of SF as a nutritional strategy for CH4 mitigation, and to determine the effects of different feeding systems (TMR and SF) on the rumen microbiome and associated metagenome of two different breeds, and on CH4 emissions. We randomly allocated four Holstein (305 ± 29 kg) and four Hanwoo steers (292 ± 24 kg) to two groups; the steers were fed a commercial concentrate with tall fescue (75:25) as TMR or SF, in a crossover design (two successive 22-day periods). Neither feeding systems nor cattle breeds had an effect on the total tract digestibility of nutrients. The TMR feeding system and Hanwoo steers generated significantly more CH4 (P < 0.05) and had a higher yield (g/d and g/kg dry matter intake [DMI]) compared to the SF system and Holstein steers. A larger rumen acetate:propionate ratio was observed for TMR than SF (P < 0.05), and for Hanwoo than Holstein steers (P < 0.001), clearly reflecting a shift in the ruminal H2 sink towards CH4 production. The linear discriminant analysis (LDA) effect size (LEfSe) revealed a greater abundance of operational taxonomic units (OTUs) related to methanogenesis for Hanwoo steers compared to Holstein steers. Kendall’s correlation analysis revealed wide variation of microbial co-occurrence patterns between feeding systems, indicating differential H2 thermodynamics in the rumen. A metagenome analysis of rumen microbes revealed the presence of 430 differentially abundant genes, among which 17 and 27 genes exhibited positive and negative associations with CH4 production, respectively (P < 0.001). A strong interaction between feeding system and breed was observed for microbial and metagenomic abundance. Overall, these results suggest that the TMR feeding system produces more CH4, and that Hanwoo cattle are higher CH4 emitters than SF and Holstein cattle, respectively. Interestingly, host-associated microbial interactions differed within each breed depending on the feeding system, which indicated that breed-specific feeding systems should be taken into account for farm management.